DIAGNOSTIC ASSESSMENT AND DEVELOPMENT OF LOGIC SKILLS IN FIRST-YEAR STUDENTS - Tertychny-Dauri, Vladimir; Мilovanovich, Ekaterina; Tanchenko, Julia; Kondrashova, Natalia; Valitova, Yulia; Morozova, Anzhelika (Revista Inclusiones, 2020)
Today first-year university students have poor logic skills, which results in their equally poor performance in mathematics and low learning motivation. The aim of the present study was to carry out a diagnostic assessment among students to detect the level of their logic skills and to identify the conditions needed to develop them to the fullest extent possible. The respondents were 53 first-year university students who were proposed to take a test including five main types of mathematical problems. The research findings showed that the students were unable to argue and to prove due to the lack of oral skills. They had difficulty in providing the specification of a subject by factor, in identifying the similarities and differences of mathematical objects and subjects and many more. In view of the above, the authors’ recommendations in respect of the intensification of oral activities in mathematics classes, summarized after the research study was over, will be in high demand not only among university, but also high school mathematics teachers because it is in high school that the learner’s logic skills begin to develop